Chaetomitrium Lanceolatum - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Plants are small, densely branched; (3) stem leaves are somewhat flattened and concave with plane apices; (3) leaf margins are sharply denticulate to serrate with simple teeth; (4) lamina cells are laxly prorate to spiculose-prorate above and smooth below; (5) setae are 9 mm long, densely papillose but smooth at extreme base; (6) capsules are inclined to horizontal and rough; (7) calyptrae are cucullate, densely hispid, and naked at the base.